Pemberdayaan Literasi Digital Warga Desa Wisata Sukajadi terhadap Kuasa Algoritma Media Sosial - Olifia, Sandra; Kurniawan, Herik (Jurnal Pustaka Dianmas, 2025)
This service activity aims to improve the digital literacy of the residents of Sukajadi Tourism Village by fostering resistance and resilience to the power of social media algorithms, especially TikTok. The approach used includes citizen counseling with lecture delivery methods involving situation analysis, needs surveys, interactive workshops, and field assistance to build critical awareness of algorithmic mechanisms, content personalization, and the risk of addiction and information manipulation. Participants consisted of villagers of social media users across ages who were selected based on digital engagement and potential social impact. The results showed an increase in participants' understanding of how algorithms work, the ability to recognize bubble filters and echo chambers, as well as digital resilience practices such as privacy settings, selection of information sources, and management of usage time. The intervention also encourages the formation of sustainable local discussion groups to share digital literacy strategies with each other. Recommendations include strengthening educational modules on algorithms, advanced training for local facilitators, and assistance in accessing digital learning resources so that the impact of empowerment can be sustainable and strengthen citizens' capacity in facing the dominance of digital platforms.